AN ANALYSIS OF WORD FORMATION USED IN I AM MALALA NOVEL BY MALALA YOUSAFZAI - Kadek Dian Asvini; Ni Nyoman Padmadewi (Undiksha Press, 2023)
This study aims to analyze the types and the most dominant type of word formation process used in a novel entitled I Am Malala by Malala Yousafzai. A qualitative descriptive is used as a research design. The data consist of words that experience word-formation process. This study analyzed words using Yule's (2006) theory. Coinage, Suppletion, Compounding, Blending, Clipping, Back-Formation, Conversion, Acronym, Derivation, and other processes were included. There are seven of nine word-formation types found from the data analyzed. The results of this study show that 633 words experience the word-formation process. Five words of coinages (0. 79%), 34 words of suppletion (5. 37%), 130 words of compounding (20. 55%), 5 words of clippings (0. 79%), 14 words of back-formations (2. 21%), 53 words of acronyms (8. 37%) and 392 words of derivations (61. 92%). The most prevalent type of word formation found is derivation. It comprises 61.92% of the general term. Derivation has 392 words out of 633 words. Keywords: word-formation process, novel, Malala